Proteção elétrica em subestações: uma abordagem sobre a energia incidente - Filipe Barcelos Resende (2016)
Good health and safety practices advocate intervention in de-energized electrical installations as the first and best option for workers. However, it is not possible to meet this premise for the full range of existing activities, at the risk of not meeting the physical availability required for the operation required by a given facility. In this way, interventions in energized installations must always be supported by effective control measures to mitigate the risks that exist during the activities. One of the main risks associated with electricity activities is the incident energy resulting from an electric arc. The objective of this work is to describe the phenomenon of the arc, to present the mathematical modeling for the calculation of the incident energy and to apply the methodology to determine the incident energy levels of a real installation. The work also presents the main ways of mitigating the risks associated with incident energy and the need for the correct specification of the fire retardant clothing to protect of the thermal effects